Capability of processed EEG parameters to monitor conscious sedation in endoscopy is similar to general anaesthesia. Issue 3 (11th February 2021) - Garbe, Jakob; Eisenmann, Stephan; Kantelhardt, Jan W.; Duenninghaus, Florian; Michl, Patrick; Rosendahl, Jonas
Abstract: Background: Reliable and safe sedation is a prerequisite for endoscopic interventions. The current standard is rather safe, yet, an objective device to measure sedation depth is missing. To date, anaesthesia monitors based on processed electroencephalogram (EEG) have not been utilised in conscious sedation. Objective: To investigate EEG parameters to differentiate consciousness in endoscopic propofol sedation. Methods: In total, 171 patients aged 21–83 years (ASA I–III) undergoing gastrointestinal and bronchial endoscopy were enrolled. Standard monitoring and a frontotemporal two‐channel EEG were recorded. The state of consciousness was identified by repeated requests to squeeze the investigator's hand. Results: In total, 1132 state‐of‐consciousness (SOC) transitions were recorded in procedures ranging from 5 to 69 min. Thirty‐four EEG parameters from the frequency domain, time‐frequency domain and complexity measures were calculated. Area under the curve ranged from 0.51 to 0.82 with complexity and optimised frequency domain parameters yielding the best results. Conclusion: Prediction of the SOC with processed EEG parameters is feasible, and the results for sedation in endoscopic procedures are similar to those reported from general anaesthesia. These results are insufficient for a clinical application, but prediction capability may be increased with optimisation and modelling. Key Summary: Electroencephalogram (EEG)‐based anaesthesia monitors, like the Bispectral Index, have been investigated as an adjunct to monitor propofol sedation in the endoscopy ward. These studies showed very limited benefit. Capability of processed EEG parameters to differentiate the state of consciousness (SOC) in endoscopy is similar to general anaesthesia. However, artefacts arising from the less controlled endoscopy environment as compared to anaesthesia limit their use in sedation monitoring. The Bispectral Index and its underlying parameters are ineffective in the determination of the SOC in sedation during endoscopic procedures.